2007
DOI: 10.1111/j.1464-410x.2007.07088.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cranberries on infection‐induced oxidative renal damage in a rabbit model of vesico‐ureteric reflux

Abstract: OBJECTIVE To evaluate the protective effects of cranberry fruit, which have known antioxidant effects, on infection‐induced oxidative renal damage in a rabbit model of vesico‐ureteric reflux (VUR). MATERIALS AND METHODS In all, 36 New Zealand male rabbits were divided into five groups, with a sham operation in four rabbits serving as the control (group 1). To create unilateral VUR the roof of the left intravesical ureter was incised, and VUR confirmed 2 weeks after surgery. In all, 32 rabbits with VUR were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Drawing firm conclusions about the role cranberry plays in cytokine production is premature, yet the data suggest that cranberry contributes to an anti-inflammatory effect. Cranberry proanthocyanidins have been suggested as being anti-inflammatory in in vitro studies [38,39] and in rabbits [7]. One human intervention study showed that the level of urinary IL-6 was reduced in pregnant women who consumed cranberry juice compared to a placebo [8], yet other cytokines measured in that study did not achieve statistical significance, perhaps due to the small n of each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing firm conclusions about the role cranberry plays in cytokine production is premature, yet the data suggest that cranberry contributes to an anti-inflammatory effect. Cranberry proanthocyanidins have been suggested as being anti-inflammatory in in vitro studies [38,39] and in rabbits [7]. One human intervention study showed that the level of urinary IL-6 was reduced in pregnant women who consumed cranberry juice compared to a placebo [8], yet other cytokines measured in that study did not achieve statistical significance, perhaps due to the small n of each group.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have shown the effects of cranberry on immune function in diverse ways: in a rabbit model of infection-induced oxidative renal damage, cranberry reduced inflammation [7]; consumption of a cranberry beverage in a human intervention study resulted in a reduction in pathogen in 42% of the subjects without altering normal vaginal microbiota [6]; lower levels of urinary IL-6 were found in pregnant women after drinking cranberry juice for at least 3 days [8]; and an enhanced generation of anti-lymphoma antibodies was detected in an immuno-competent mouse model of lymphoma [9]. Recent studies have shown effectiveness of cranberry in reducing reoccurrence of urinary tract infections [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Although rats are more economical than larger animals, the latter are much easier to handle. Moreover, the surgical procedure of open bladder incision of the intravesical ureteral tunnel is well established in the rabbit (5, 10). …”
Section: Discussionmentioning
confidence: 99%
“…However, as with anthocyanins glycosides, that may contribute to the clinical symptom‐improving effect of cranberry preparaions (Hidalgo et al, 2012), plasma and urine concentrations of the co‐active compounds will be very low (Howell, , Milbury et al ., ). In a rabbit model of vesico‐ureteric reflux, consumption of cranberries had a protective effect on E. coli ‐induced oxidative renal damage (Han et al ., ).…”
Section: Mechanism Of Actionmentioning
confidence: 97%